Criminal Liability of Military Members as Perpetrators of Criminal Acts of Abuse Resulting in Death (Decision Study Number: 83-K/PMT-II/Bdg/AD/VII/2024) - Sukardi, Sukardi; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Assault is a common and easily occurring offense in society. The consequences of such criminal acts are widespread and frequent, with many cases resulting in the victim's death. Therefore, the punishment demanded for perpetrators must truly reflect a sense of justice for the victims. However, what hapens if the perpetrator of an assault resulting in death is a member of the military, an institution under the Indonesian military command structure? The purpose of this study is to examine and analyze the legal construction of criminal liability for military personnel as perpetrators of assault resulting in death, and to investigate the judicial considerations made by judges in sentencing military members convicted of such offenses. This research falls under the category of normative or doctrinal legal research. The term "doctrinal" derives from the word "doctrine," meaning legal principles or norms that are adhered to. The construction of criminal liability for military personnel who commit assault resulting in death illustrates the complexity between the general criminal law system and military criminal law. Although military personnel are subject to the military legal system, the principles of legality and criminal liability remain universally aplicable. In Decision Number 83-K/PMT.II/BDG/AD/VII/2024, there was a discrepancy between the indictment under Article 351 paragraph (3) of the Criminal Code and the verdict, which only aplied Article 351 paragraph (1) of the Criminal Code. This raises concerns of potential violations of the due process of law and the principle of legal certainty. On the other hand, the judge considered juridical aspects, such as the alignment between the indictment, evidence, and witness testimony, to determine the fulfillment of criminal elements. Non-juridical considerations were also taken into account, including the background of the defendant, social impact, and the defendant's cooperative attitude and remorse during trial. Thus, the judge's ruling reflects a combination of legal, moral, and institutional considerations aimed at upholding justice and preserving the integrity of the Indonesian National Armed Forces (TNI).